Optimizing Sharia-Based Product Production and Quality Aspects in Halal Food MSMEs in Madura - Ach. Jailani; Beryl kholifurrahman; Mashudi (Al-Iffah: Journal of Islamic Sciences Research, 2025)
The purpose of this study is to examine how halal food micro, small, and medium enterprises (MSMEs) in Madura strive to optimize the production and quality of their Sharia-compliant products. This study is based on the high public demand for high-quality, safe-to-consume halal food products that meet halal standards. The research method used was literature review; references were collected, researched, and analyzed from various relevant articles, journals, and books discussing Sharia principles, quality control, and the halal food production process. The study results indicate that optimizing production aspects in halal food MSMEs can be achieved through the implementation of Sharia-compliant standard operating procedures (SOPs), the selection of halal raw materials, and improving the cleanliness and efficiency of the production process. Meanwhile, product quality improvements can be achieved through quality standardization, attractive packaging, and halal certification. With this optimization, halal food small and medium enterprises (MSMEs) in Madura are expected to be able to compete in a wider market and increase customer trust in high-quality, Islamically compliant halal products.